PENINGKATAN PERFORMA DETEKTOR PENCURI IKAN DENGAN KALMAN FILTER DI KERAMBA APUNG GILI KETAPANG - Mahdiyafi Rahardicahya; Akhmad Zainuri; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2023)
Gili Ketapang Island is one of the strategic areas for marine conservation in East Java, offering various main activities such as snorkeling, diving, recreational fishing, religious tourism, both traditional and modern fishing, and the development of marine cultivation through floating net cages. Floating net cages are becoming increasingly popular as a method of fish cultivation in Indonesia. However, fish theft in floating net cages remains a frequent and significant problem for fish farmers, causing substantial losses. Therefore, a fish theft detection device is needed to help reduce cases of fish theft in floating net cages. In order to develop this fish theft detection device, the use of PIR sensors and accelerometers is required. PIR sensors detect human movements entering or exiting the sensor's range, while accelerometers are used to measure the angles generated by ocean waves, which will be set as triggers for the PIR sensor. The characteristics of PIR sensors and accelerometers are crucial indetermining the accuracy and reliability of the fish theft detection device. Therefore, in-depth research on the characteristics of PIR sensors and accelerometers to be used in the fish theft detection device in floating net cages is necessary. As a result, it is expected that the detection device will work effectively and assist fish farmers in preventing fish theft in floating net cages. Keyword: Gili Ketapang Island, Fish Theft, Floating Net Cages, PIR Sensor, Accelerometer